Can Low‐Cost Strategies Improve Attendance Rates in Brief Psychological Therapy? Double‐Blind Randomized Controlled Trial. Issue 12 (1st October 2015) - Delgadillo, Jaime; Moreea, Omar; Murphy, Elizabeth; Ali, Shehzad; Swift, Joshua K.
Abstract : Objectives: To assess if telephone text message appointment reminders and orientation leaflets can increase the proportion of patients who attend brief interventions after being assessed as suitable for guided self‐help following cognitive behavioral therapy principles. Method: Attendance was operationally defined as having accessed at least 1 therapy appointment. A secondary outcome was the proportion of attenders who completed or dropped out of therapy. After initial assessment, 254 patients with depression and anxiety disorders were randomly assigned to 1 of 3 groups: (a) usual waitlist control, (b) leaflet, (c) leaflet plus text message. Differences in the proportions of patients who started and completed therapy across groups were assessed using chi‐square and logistic regression analyses. Results: Overall, 63% of patients in this sample attended therapy. Between‐group differences were not significant for attendance, x 2 (2) = 3.94, p = .14, or completion rates, x 2 (2) = 2.98, p = .23. These results were not confounded by demographic or clinical characteristics. Conclusions: Low‐cost strategies appear to make no significant difference to therapy attendance and completion rates.